Phenolic Aminocarboxylic Acids as Gallium-Binding Radiopharmaceuticals - Hunt, F. C. (Nuklearmedizin - NuclearMedicine, 1984)
The phenolic aminocarboxylic acids ethylenediamine di [o-hydroxyphenylacetic acid] (EDDHA) and N,N’bis [2-hydroxybenzyl] ethylenediamine N,N’-diacetic acid (HBED) form gallium complexes having high stability constants which enable them to resist exchange of gallium with plasma transferrin. 67Ga complexes were synthesized with these ligands, placing substituent groups in the phenolic ring to direct excretion via the renal or hepatobiliary route. The amount of 67Ga-Br-EDDHA excreted via the hepatobiliary route was comparable with that of some of the 99mTc agents. Excretion of 67Ga-Br-HBED was similar but with delayed transit from the liver. 67Ga COOH-EDDHA was excreted exclusively via the renal route. These findings provide a basis for developing new 67Ga or 68Ga radiopharmaceuticals, the latter for use in positron emission tomography, using these phenolic aminocarboxylates.